International Legal Regulation of Military Outer Space Activities - A. I. Antonov (Vestnik MGIMO-Universiteta)
The publication is devoted to legal issues and prospects of banning weapons in outer space. The international legal basis currently existing in this field governs only certain aspects of use of outer space for military purposes, and it is obviously not enough to prevent the emergence of weapons in outer space. Attempts on the international level in recent years to put legal provisions in place that would establish barriers to an arms race in outer space so far have not been successful. The time is ripe to implement initiatives contributing to the institutionalization of verification activities on non-weaponization of outer space